2021
DOI: 10.1111/cxo.13114
|View full text |Cite
|
Sign up to set email alerts
|

Management of open‐angle glaucoma by primary eye‐care practitioners: toward a personalised medicine approach

Abstract: Glaucoma is the leading cause of irreversible blindness worldwide. As a chronic disease, glaucoma presents a significant burden to the individual, health-care provider and the health-care system. Currently, strategies for treating glaucoma are focused on lowering intraocular pressure, which is aimed at slowing or arresting disease progression over time. This is the only current accepted therapeutic strategy for glaucoma, and can be achieved using topical drugs, laser trabeculoplasty, filtration surgery or cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 246 publications
(222 reference statements)
0
14
0
Order By: Relevance
“…Since the 24-2C can in most cases identify the presence of central visual field defects -but not necessarily "clusters", when might the 10-2 be clinically useful for the individual patient as part of a personalised management plan? 51,52 Three representative examples of subjects used in the present study are shown in Figure 5, describing the diverse possible outcomes of glaucomatous visual field defects, which despite instances of mutually identified or suspected defects. Therefore, identification of central visual field defects on 24-2 or 24-2C could provide an indication for conducting the 10-2 to confirm or fully characterise the defect.…”
Section: Practical Considerations For Central Visual Field Testingmentioning
confidence: 99%
“…Since the 24-2C can in most cases identify the presence of central visual field defects -but not necessarily "clusters", when might the 10-2 be clinically useful for the individual patient as part of a personalised management plan? 51,52 Three representative examples of subjects used in the present study are shown in Figure 5, describing the diverse possible outcomes of glaucomatous visual field defects, which despite instances of mutually identified or suspected defects. Therefore, identification of central visual field defects on 24-2 or 24-2C could provide an indication for conducting the 10-2 to confirm or fully characterise the defect.…”
Section: Practical Considerations For Central Visual Field Testingmentioning
confidence: 99%
“…Current management paradigms for glaucoma, a leading cause of irreversible blindness worldwide, emphasize two main goals: first, to preserve vision and prevent irreversible vision loss, and, second, to preserve quality of life by balancing treatment decisions against the potential impact of disease. 1 3 Individualizing the glaucoma treatment plan involves interpreting the clinical findings to understand the individual's disease trajectory. Disease progression in glaucoma is often quantified using visual field testing over time, as perimetry results have been strongly correlated with an individual's functionality and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 3 million Americans have glaucoma, a major cause of irreversible blindness with no cure [ 59 , 60 ]. Even with therapeutic intervention, approximately 10% of those diagnosed still experience vision loss [ 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…An estimated 3 million Americans have glaucoma, a major cause of irreversible blindness with no cure [ 59 , 60 ]. Even with therapeutic intervention, approximately 10% of those diagnosed still experience vision loss [ 59 , 60 ]. Although not always elevated, intraocular pressure (IOP) is currently the only treatable factor of the disease.…”
Section: Resultsmentioning
confidence: 99%